Ideas sobre los gases en alumnos de 10 a 15 años - Furió-Mas, Carles (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This paper shows some ideas the students have on specific perceptive aspects of gases, such as their materiality or the volume they take, together with the analysis of their answers to their internal structure. The results found are similar to those obtained from other context. It is confirmed that students maintain an urisioielic vision of the substantiality of gases, thcitigh some features of the particulate theory (accepted at present as for their internal structure) equally appear.